Inovasi Safety School: Mengulik Spiritual Learning pada Madrasah Permodelan di Lombok, Indonesia - Ahyar; Faizah (Edukasia Islamika : Jurnal Pendidikan Islam, 2019)
The concept of ‘safety school’ emerges from the phenomenon of juvenile delinquency, such as the existence of students truant, coming late, smoking, drugs, gadget inspection, radicalism proliferation, and insufficient understanding of nationalism. To respond to this growing need, two public junior high schools in Mataram, Indonesia, exist as madrassas that foster ‘zero accident’ education. Grounded in a qualitative case study, this study explores how the two madrassas promoted positive behavior through the innovation of safety school. As a result, the two Islamic educational institutions did not lose their school identities that uphold the value of spirituality. Data were garnered through in-depth interviews and observation. Findings of this study show that in responding to this challenge, the two pilot madrassas proposed safety school innovations. They were not only supported by physical innovations, such as CCTV facilities, security, well-built school wall, determined school rules, and maintenance of madrasa buildings, but are also supported by non-physical innovation, namely: spiritual learning. It was demonstrated in a set of components of religious programs, such as the dhuha and dhuhur prayer and, the environmental care movement, one day one verse program, the strengthening the Qur’an tajweed and Tahfiz the Qur’an, Imtaq (iman and taqwa) program, community-based madrasa, and the use of religious laboratories.